Menuntut Hak Atas Kota Baru: Klaim (Kembali) Lahan oleh Petani di New Clark City - Jerome Christopher Samson Flores (Badan Strategi Kebijakan Hukum, 2024)
New cities, often designed as development strategies, cause dispossession, displacement, and disruption of everyday lives of local communities. To further explore the effects of new cities and urban development in the Global South, this study explores the realities of farmers whose homes and livelihoods are affected by the construction of New Clark City in the Philippines. Employing the concept of the right to the city by Henri Lefebvre, this study delves into the farmers' agency in reclaiming space in the city being built on their rice fields. Through qualitative research methods, including interviews and participant observation, the study elucidates the strategies employed by farmers to assert their right to New Clark City. Highlighting that (re)claiming of space by the farmers is motivated by their need to make a living and provide for their families, the study builds on the understanding of the right to the city as the right of the inhabitants to shape their environment and manage their resources. Although the right to the city heavily depends upon the collective power to reshape the process of urbanization, the article argues that it can also be asserted through individual and unorganized actions.